Political communication: uncovering knowledge, attitudes and young voters’ readiness for PRU-15 in Batang Padang district, Perak - Siti Nor Amalina Ahmad Tajuddin,; Joekryno Joni,; Khairul Azam Bahari, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysia made history when the Dewan Rakyat approved an amendment to the Federal Constitution that lowered the voting age from 21 to 18 years old. The country’s democratic system was colored by the automatic registration of those who turned 18 as voters for the 15th Malaysian General Election (GE-15). This amendment aims to democratize the political process in this nation and promote mature, fair, and equitable elections. This ongoing study aims to discover young voters' knowledge, attitudes, and readiness toward the 15th general election (PRU-15) in Batang Padang, Perak district. Methodologically, a quantitative approach was used where 462 youth participants completed questionnaires. The findings discovered that although attitudes and readiness among young voters in the research population are at a moderate level, they have a high level of knowledge. The result also uncovered five key factors that influence young voters’ readiness towards making their decisions for PRU-15 namely voting is my responsibility, the good reputation of elected representatives, peer influence, the implementation of the Undi-18 policy by the government and family support. The study thus contributed to a new landscape of political communication through young voters’ contribution not only to casting the ballot during the election but also to participating in the country’s leadership as members of parliament.